PENERAPAN MODEL PEMBELAJARAN POE UNTUK MEREMEDIASI MISKONSEPSI SISWA SMP NEGERI 23 PONTIANAK - Teguh, Istnan Dikdoyo; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know the influence of the application of the POE (predict, observe, explain) learning model to remediate misconception of students on the material light reflection in junior high 23 State of Pontianak. The form of this research is pre-experimental design with one- group pre test post- test design. This research involves 28 students IX as sample that selected by intact group.The tool collecting data in the form of diagnostic tests in the form of multiple choice accompanied by a reason. Average change of misconception for all Mc Nemar test based on the question of the obtained results of Ï‡2hitung > Ï‡2tabel (3.84), then a change occurred after significant student misconceptions implemented remediation. In addition, the effectiveness of remediation using a model learning POE using the formula obtained price proportion to decrease the amount of misconception (0.59). So conclusion remediation using a model learning POE influential in reducing the misconception of students on the material reflection of light. The result of this research are expected to be an alternative in an attempt to remediate misconception that experienced students.Â Keywords:Â Remediation, Misconception, POE (predict, observe, explain) Learning Model, Material Light Reflection